Trains in Literature - Huková, Petra (Univerzita Pardubice, 2020)
The work deals with the roles of the trains and railways in literature, namely in crime fiction and parody narratives by Agatha Christie, Victor L. Whitechurch and Jára Cimrman. The development of British railways in the 19th century is outlined regarding the social and cultural impacts on the society. The time period and literary context of the selected authors are described taking the publication dates of the works into consideration, and literary devices used by the authors to depict trains, mystery plots and parody are described.
Vlaky v literatuře
Keywords: vlaky; železnice; detektivky; fikce; parodie; Christie, Agatha; trains; railways; crime; fiction; parody; Christie, Agatha